Ambidexterity and Firm Performance: A Literature Review - Feng ZHANG (Management and Economics Review)
This study reviews extant literature on ambidextrous mechanisms, contingencies impacting the relationship between organisational learning activities and performance, and aggregation issues in studying ambidexterity. The review identifies a largely neglected factor by the extant literature in determining and clarifying the relationship between ambidextrous organisational learning and firm performance, namely, intra-firm distribution of organisational learning activities. Building upon the literature review, this study recommends future research directions associated with the intra-firm distribution of organisational learning activities to advance our understanding of firm strategic deployment of ambidexterity.